The Oxford handbook of international business strategy - Mellahi, Kamel; Meyer, Klaus; Narula, Rajneesh, 1963-; Surdu, Irina; Verbeke, Alain (Oxford : Oxford University Press, 2020)
Multinational enterprises must contend with increasingly challenging conditions in the international business environment. This handbook explores how classic principles of international competitive strategy are transformed in today's markets and provides suggestions on how firms can develop effective strategies to respond to these transformations.
The Theory of International Business Strategy / Rajneesh Narula, Alain Verbeke, Wenlong Yuan -- It's Not Only the International New Venture But (Also) the Micro-Multinational, Daftie! Reconsidering the Unit of Analysis in International Entrepreneurship / Pavlos Dimitratos -- Internationalization of Family Firms: When is a Managerial Focus on Socio-Emotional Wealth Effective? / Liena Kano, Alain Verbeke, Luciano Ciravegna -- Internationalization of Emerging-Markets Multinationals: The Role of the Underdevelopment of the Home Country / Alvaro Cuervo-Cazurra, Alicia Rodríguez, C. Annique Un -- State-Owned Multinational Enterprises: Theory, Performance and Impact / Saul Estrin, Jing Li, Daniel M. Shapiro -- Dynamics of Operation Modes: Switches and Additions / Gabriel R. G. Benito, Bent Petersen, Lawrence S. Welch -- Subsidiaries as Sources for Learning in Multinational Enterprises: A commentary on the Importance of External Embeddedness / Ulf Andersson, Mats Forsgren, Ulf Holm -- Political Strategies of Subsidiaries of Multinational Enterprises / Maria A. De Villa -- Looking Back to Move Forward: An Overview of Foreign Divestment Decisions / Carlos M. P. Sousa, Qun Tan -- Foreign Market Re-entry Strategies: The Role of Cognitive Biases in Decision-Making / Irina Surdu -- Digitalization and its Strategic Implications for the Multinational Enterprise: The Changing Landscape of Competition and How to Cope with it / Pinar Ozcan, Basak Yakis-Douglas -- International Business History and the Strategy of Multinational Enterprises: How History Matters / Geoffrey Jones, Teresa da Silva Lopes -- Corporate Social Responsibility, Irresponsibility and the MNE Environment / Giulio Nardella, Stephen Brammer -- Global Value Chain Governance: A MNE Capabilities View / Anthony Goerzen, Ari Van Assche -- Sustainability Strategies: Research and Practice in International Business / Renato J. Orsato, Simone R. Barakat, José Guil
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 9, 2020).
Keywords: International business enterprises -- Management; Strategic planning; Business planning